Investigation of shaded pole stator topology for low power AC motors design - Lidija Petkovska; Goga Vladimir Cvetkovski (Emerald, 2024)
Purpose:This paper aims to investigate the features of single phase shaded pole stator with squirrel–cage rotor or permanent magnet rotor, that leads to an investigation of these topoloties as induction motor or synchronous motor. The comparative analysis is realised for the following three topologies: single phase shaded pole induction motor (SPIM) with squirrel–cage rotor, the second topology (single phase synchronous motor) has the same stator configuration but with permanent magnet rotor and the third investigated topology is similar to the second one, where the stator poles instead of iron steel are made of soft composite material.Design/methodology: The investigation in this work starts with a performance analysis of single-phase SPIM. Afterwards for the same stator topology the squirrel rotor is replaced with a two-pole permanent magnet rotor and the same performance analysis is realised for this topology. Finally, the second topology is improved bay replacing the iron steel stator poles with stator poles made of soft magnetic composite material and performance analysis is realised for this third type of topology as well. The performance analysis of all topologies is realised by implementation of finite element method and finite element analysis.Finding: The presented data and diagrams from the realized investigation show that single phase synchronous motor with shaded pole stator has an improved characteristics in comparison with the initial single-phase SPIM. Finally, the third topology realized on the bases of the single-phase synchronous motor has the best performance characteristics due to the implementation of soft magnetic material in the realization of the stator poles. The proposed methodology for structural and performance improvement of a single-phase SPIM topology opens the possibility for additive manufacturing application and significant cost reduction.Originality/value: The focus was put on exploration the possibilities of the single-phase shaded pole stator topology for application in low-power and low-cost single phase self-starting motors. By simple replacement of the squirrel–cage rotor, in the reference AKO-16 motor, with one-piece ferrite permanent magnet rotor, the self-starting single phase synchronous motor was derived. In the next step, owing to simplify the SPPM motor production process and manufacturing, the stator poles instead of iron steel lamination were made of soft composite material Somaloy®. It opens the possibility for additive manufacturing application and significant cost reduction.